An Analysis of Translation Techniques Between Students and Chat-Gpt In Translating Sarcasm and Irony In The Gadis Kretek Novel - Sianipar, Nelly Noviana; Sipayung, Kammer Tuahman; Octavianna, Yessy (Lembaga Riset dan Inovasi Almatani, 2025)
The purpose of this study aims to analyze the translation techniques used between Students and Chat-GPT in translating sarcasm and irony. This study is expected to provide a better understanding of the strengths and weaknesses of each translation technique. Moreover, it can provide new insights into the application of machine translation in cultural and literary contexts, such as the translation of sarcasm and irony which often have certain cultural nuances and expressions. The author also suspects that the translation of the source language to the target language through Chat-GPT may cause many differences and debates if the translation containing sarcasm and irony is misinterpreted. This research is conducted using Qualitative Descriptive method. The data source of this research is sarcasm and irony sentences taken from Gadis Kretek Novel. The author took students data samples and Chat-GPT to translate fifty sentences containing sarcasm and irony in Gadis Kretek novel by Ratih Kumala (2012). Student translators used eight translation techniques, that is literal translation (82 data), modulation (34 data), adaptation (9 data), transposition (9 data), amplification (7 data), established equivalent (12 data), calque (7), reduction (1 data). Meanwhile, Chat-GPT translators used six translation techniques, that is modulation (26 data), literal translation (15 data), adaptation (4 data), borrowing (2 data), transposition (2 data), amplification (1 data). This data proves that student translators and Chat-GPT have different abilities in choosing the translation techniques used. This study is expected to be useful for readers to emphasize the importance of understanding context and meaning in choosing the right translation technique.